Keep the hope alive: young Indonesian musicians' views of the future. (28th May 2017) - Sutopo, Oki Rahadianto; Nilan, Pam; Threadgold, Steven
ABSTRACT: Using ethnographic and interview data, this article explores hopes for the future of young Indonesian musicians. The young people are seen to consider their future trajectories in multiple, hierarchical music fields. The article also takes into account the ontological insecurity of jobs as a professional musician, arguing that there is continuous reproduction of a doxa, namely 'survival of the fittest' in Indonesia. Yet despite abundant risks to livelihoods, young Indonesian musicians expressed optimistic views about the future. The analysis of data below bridges the gap between the traditionally separate youth studies fields of youth transitions and youth cultures. Our interpretation critically contextualises the dialogue between these two fields based on the experiences of young Indonesian musicians as a part of the Global South.